Building Public Trust Through E-Governance Strategy: Case Study in DKI Jakarta, Indonesia - Nurmala Fairuzyah, Intan; Ahmad Arkaan, Gibran; Alfath Marfariza, Haekal; Meisya Indira Putri Suhendar; Syifa Khoirunnisa (GoResearch - Research & Publishing House, 2024)
E-governance has emerged as a strategic approach to address governance challenges in Indonesia by enhancing transparency, efficiency, accountability, and public participation. This study explores the implementation of e-governance in Indonesia, emphasizing its role in building public trust and transforming traditional governance into a digital system. Using a qualitative approach with literature study as the primary method, the research analyzes various initiatives, including Smart City programs and digital applications like JAKI and Open Data Jakarta. These efforts have demonstrated significant potential in improving public services and fostering government transparency.The study identifies several key components critical to successful e-governance, such as robust ICT infrastructure, supportive policies, and active public involvement. Despite notable progress, challenges persist, including digital divides, limited ICT access in remote areas, insufficient integration of governance systems, and low digital literacy among civil servants and the public. Issues of data security and privacy further underscore the need for a comprehensive strategy. Case studies, particularly in Jakarta, highlight effective implementations and innovations under various leaderships that significantly improved governance and public trust. However, sustaining these improvements requires addressing systemic barriers, fostering cross-sector collaboration, enhancing human resource capabilities, and promoting digital literacy. This study concludes that while e-governance has transformative potential, its success in Indonesia depends on overcoming infrastructural and cultural challenges. With continuous improvement and collaboration, e-governance can lead to a more transparent, responsive, and accountable government, reinforcing public trust and participation in the democratic process.